Analisis Nilai Pelanggan Listrik Prabayar Terhadap Kepercayaan Pelanggan Serta Implikasinya Pada Citra Perusahaan PT PLN Bright Batam - Renniwaty Siringoringo; Putu Hari Kurniawan (LPPM Universitas Putera Batam, 2018)
Innovative service quality, basically take form reputable technology information which the activity is create the “recharge electricity program” that have objection to effectivity and make it easier to operate. Such as acces and manage the using electricity for this day. But its positivelly response by batam citizen , the aim of this research is to measures the customer value how far the relationship mediated with image corporate. this research is evaluated to measuring how much level of public trust rendered against his visit for program conducted by pln bright batam as indicated by variable the value of customers and its implications on the image of state-owned electricity company pln was bright batam as a public company. How ever the variable is implicate for further study to increasing the image position PT PLN bright Batam as a public service corporation. The population research is the customer electricity prepaid households across seven district in Batam which ones with samples from 7 200 respondents and engineering the sample collection using proportional. sampling techniquesThe research is explanatory survey to analyze how big the influence and the relations among a variable whose, customers confidence in image of companies .This object of study is a customer of the recharge electricity take from 200 household responden in 7 district in Batam. This research used Structure Equation Model (SEM) as model analysis which for operate data mining used Lisrel 8.8 for windows. The result of this study observed variabel significantly positively to laten variabel such as customer value, trust, and Image. Customer Value has positive and significantly effect on trust and image.